Robotics in Education. A Survey Report: A Case Study - Smyrnova-Trybulska, Eugenia; Staniek, Dawid; Zegzuła, Dominika (International Journal of Research in E-learning, 2020)
This article analyses various aspects of using robotics in education and examines the level of preparation and motivation of children and pupils. The authors carry out a comprehensive review of research and scientific publications regarding technological, didactical, methodological, and human aspects of using robotics in education. The article presents a report on a survey on pupils’ opinion on robotics in education, which was conducted during the third Silesian Science Festival, and discusses the exhibition stand presenting innovative digital technologies and methods in education and business as well as Photon robots.